PTH-053 Vitamin D and other micronutrient status in patients with ald and other liver diseases. (23rd September 2015) - Raychaudhuri, C; Al-Joudeh, A; Srinivas, M; Ellis, B; Bardhan, K D; Willemse, P J; Basumani, P; Höroldt, B
Abstract : Introduction: Vitamin D deficiency is associated with non-specific symptoms, carries long-term risk to bone health, and certain groups are at higher risk (alcohol excess, old age, Asians). The prevalence among patients attending hepatology clinics is unclear; this prompted our pilot study. Methods: Measurements: vitamin D, calcium profile, LFT, FBC available for all; vitamin B12, folate, ferritin/iron studies available for 256 patients. Use of OTC supplements was checked and those on vitamin (other than oral thiamine or Vitamin B complex) preparations were excluded. Frequencies were compared by Fisher exact test. Results: 288 patients were included (170 male, median (range) age: 54.81 (17–92), 155 Caucasian). 113 had alcoholic liver disease (112 Caucasians), 175 other liver diseases (non-ALD: 29 autoimmune liver disease, 52 fatty liver, 65 viral liver hepatitis, 29 other). 37 patients had liver cirrhosis (29 ALD, 8 non-ALD). (a) Overall median vitamin D level was 37 nmol/l and was lower in ALD vs non-ALD patients: 30 vs 47 nmol/l. (b) Median vitamin D level in south-east Asian was 23 nmol/l, deficiency was significantly more common (50 vs 30%, p=0.02); these patients were excluded from subsequent analysis. (c) Vitamin D deficiency was significantly more common in ALD patients (33 vs 13%, p=0.001). (d) In ALD cirrhosis was not significantly associated with vitamin D deficiency (p=0.08). (e) In ALD, there was trend towards increased vitamin D deficiency in females (p=0.06), in patients over 60 years (p=0.053) and towards worsening vitamin D deficiency in spring compared to autumn (p=0.07). (f) In non-ALD, vitamin D deficiency was significantly more common in patients >60 years (p=0.02); but not in women (p=1.0). Seasonal variation was not significant for deficiency (p=0.07), but for combined deficiency/insufficiency (p=0.004). (g) In non-ALD cirrhosis, vitamin D deficiency was more common but this did not reach statistically significance (33 vs 12%, p=0.09). (h) Folate (10%) and iron deficiency (14%) were more common in ALD (non-ALD both 4%) but vitamin B12 deficiency was not (8.8 vs 8.2%). Conclusion: Vitamin D is common in ALD, it's prevalence in other liver diseases is around 12%, higher than other micronutrient deficiencies. It is increased in older subjects and South-East Asians and seasonal variation is less then expected. It should be screened for in all ALD patients and in non-ALD in those at increased risk (older age, South-East Asian and cirrhosis).